Effects of human disturbance on habitat and fish diversity in Neotropical streams - Larentis, Crislei; Kliemann, Bruna Caroline Kotz [UNESP]; Neves, Mayara Pereira; Delariva, Rosilene Luciana (Public Library of Science (PLoS), 2022)
Human pressures have been intensely modifying freshwater ecosystems worldwide. We assessed the effects of human pressure on habitat diversity and primary productivity to understand the consequences on fish fauna in 25 tropical and subtropical streams of two globally important ecoregions: Iguassu and Upper Paraná. We hypothesized that the increased human pressure (urbanization and agriculture) on stream environments, both at the local and catchment scales, directly decreases habitat diversity. We also hypothesized that increased human pressure triggers changes in primary productivity and fish fauna composition and structure. We evaluated the human pressure intensity using the Integrated Disturbance Index and the Rapid Habitat Diversity Assessment protocol, which combines information about land use, land cover and environmental characteristics of the stream catchment and sampling sites. Streams with increased human disturbance had lower habitat diversity, higher primary productivity, and high non-native species abundance. Fish compositional turnover was associated with increased human disturbance. Native and degradation-sensitive fish species, especially endemic ones, were associated with streams with higher habitat diversity and forested cover. Degradation-resistant fishes, mostly nonnative species, were associated with streams with higher human disturbance and urban land use. Although human pressure did not affect species richness, Shannon diversity, and Simpson dominance, there were significant effects on numerical abundance and fish species equitability. In this study, human pressure directly affected habitat structure, with indirect consequences for fish fauna, increasing the potential for local extirpation of rare species.